1999
DOI: 10.1038/sj.onc.1202990
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and initial characterization of the BRCA2 promoter

Abstract: The hereditary breast cancer susceptibility gene, BRCA2, is considered to be a tumor suppressor gene that may be involved in the cellular response to DNA damage. The transcript for this gene is cell cycle regulated with mRNA levels reaching a peak just before the onset of DNA synthesis. In order to de®ne the mechanisms by which BRCA2 is transcriptionally regulated, we have begun to study upstream regulatory sequences. In this report, we de®ne a minimal promoter region that has strong activity in human breast e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 55 publications
(43 reference statements)
2
60
0
Order By: Relevance
“…However, in most cells expressing wild-type p53, the level of protein is undetectable due to a rapid turnover rate. Therefore, we decided to use a cell line, such as SK-N-SH, a neuroblastoma derived cell line, which expresses wildtype p53 determined by sequencing (Davido et al, 1992) which is cytoplasmically sequestered and more stable (Moll et al, 1996;Zaika et al, 1999). We exposed SK-N-SH cells to 5 Gy IR and observed strong translocation of p53 into the nucleus within 3 h by indirect immuno¯uorescence using PAb 421 ( Figure 4A).…”
Section: Conformation Of P53 Changes In Response To Ir In A1-5 and Skmentioning
confidence: 99%
“…However, in most cells expressing wild-type p53, the level of protein is undetectable due to a rapid turnover rate. Therefore, we decided to use a cell line, such as SK-N-SH, a neuroblastoma derived cell line, which expresses wildtype p53 determined by sequencing (Davido et al, 1992) which is cytoplasmically sequestered and more stable (Moll et al, 1996;Zaika et al, 1999). We exposed SK-N-SH cells to 5 Gy IR and observed strong translocation of p53 into the nucleus within 3 h by indirect immuno¯uorescence using PAb 421 ( Figure 4A).…”
Section: Conformation Of P53 Changes In Response To Ir In A1-5 and Skmentioning
confidence: 99%
“…USF Regulates BRCA2 Basal Transcription-The Ϫ34 to Ϫ15 region has recently been reported to be responsible for regulation of the basal activity of the BRCA2 promoter (15). The USF binding site was shown to regulate promoter activity in a cell cycle-dependent manner, with binding of USF resulting in 3-fold induction of luciferase activity.…”
Section: Identification Of Regulatory Domains In the Brca2mentioning
confidence: 99%
“…Low levels of expression are detected in G 0 , G 1 , and M phase (14). Cell cycle-dependent expression has recently been associated with binding of the upstream stimulatory factor (USF) 1 protein and Elf-1 transcription factor to the BRCA2 promoter (15). In addition, BRCA2 expression is elevated indirectly in response to the mitogenic activity of estrogen, which has been associated with progression of the cell cycle (16,17).…”
mentioning
confidence: 99%
“…The location of the E box and the EBS at the vicinity of the transcriptional initiation site is documented. A functional E box has been described at position Ϫ7 to Ϫ2 from the transcriptional initiation site of the cathepsin B gene (60), as have an E box and an Ets/E2F site, respectively, at Ϫ18 and Ϫ58 bp on human BRCA2 gene promoter (56). By taking into account the close vicinity of the E boxes to the transcriptional initiation site in the context of the proximal bax promoter and the drastic effect of mutation of these E boxes on the activity of this promoter, we can suggest that the binding of Pea3 with USF-1 to these E boxes is involved in and can facilitate the formation of the transcriptional preinitiation complex.…”
Section: Discussionmentioning
confidence: 99%
“…Ets-1 and USF-1 are widely known to interact, for example, on the human immunodeficiency virus, type 1, long terminal repeat (55), on the BRCA2 promoter (56) or on the mannose receptor promoter (57). Since Greenall et al (53) have shown by an in vitro glutathione S-transferase pulldown assay, a physical interaction between USF-1 and the ETS domain of Pea3, we then confirmed by co-immunoprecipitation assay in TAC-2.1 cells that these two factors interact (data not shown).…”
Section: Discussionmentioning
confidence: 99%